The Effect of Budget Goals Clarity and Organizational Commitment on Managerial Performance(Study on Cimahi City Government, West Java Province, Indonesia) - Nuryaman,; Cecio Septiansyah, Raka; Gusnandar Arnan, Sendi (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to empirically examine the effect of clarity of budget goals and organizational commitment on the managerial performance of regional work units (SKPD). The population and sample in this study were 36 heads of organizational units spread across 9 government offices in Cimahi City. Data was collected using survey methods by distributing questionnaires. The analytical method used is Pearson correlation analysis. The results of the study showed that the clarity of the budget target and organizational commitment had a positive effect on the managerial performance of the regional work units. Managerial performance of the head of the organizational unit can be improved through increasing the organizational commitment of the head of the organizational unit and the clarity of the budget goals.